The Epr-Argument Under The Critic Of Material-Geometry & Space-Energy Universe - Georgallides, Markos (European Journal of Applied Sciences, 2024)
Distance is the Quanta in E-Geometry, while Material-point is the Quanta in Physics and Material Geometry which is the Composition of Opposites and the Elements in Chemistry and Physics. As in Algebra Zero,0, is the Master-key number for all Positive and Negative numbers, and this because their sum and multiplication become zero, and the same on any coordinate-System where, ±, axes pass from zero, the Rolling of Positive ⊕ constituent on the Negative ⊝, constituent, creates the Neutral Material Point Which Equilibrium. Its Angular momentum is identical to the Spin and consists the First-Discrete-Energy-monad which occupies, Discrete Value and Direction, in contradiction to the Point,which is Nothing, Dimensionless, and without any Direction.Quaternion [(+)↻↺(-)] ≡ Box ≡ Material Point ≡ Dipole, carries the Principal stress σ between A(+), B(-), which σ, as Centripetal-acceleration is the minimum Energy which becomes from the in Storage AB acceleration and is equal to the Gravity g. Because in-Box may exist different motions Revolving R and Periodic,P, the acceleration of Gravity g ≡ ± σ exists for the First Box- , while for the Second Box- is following the Local-Extreme-case where the acceleration of Gravity g ≡ ± σ, is the Locally altering Spin by changing the Principal-stress σ with an Local-uniform Pressure ≡ g = g * [Force/Area] = G, i.e. is proved that the minimum Local - Energy acceleration is the known Universal Gravitational-constant G = g k = g = σ = g. ≡σ. ³≡Φ[{σ Φ}≡[ ]≡2π r ≡ ≡ mg = = ] such for Macrocosm and as for Microcosm, and Obeying Newton`s Laws of motion. Photon is a Box ≡ {It is the moving Energy-Storage, r, with The Golden ratio frequencies → = [ ]. ≡ = }, Transported with Light velocity by An Electromagnetic-Radiation of wavelength λ = c / = c / It was Proved that Force G pressing, through Stress, g, to Enter the Critical-cave in Planck-length with minimum Energy creates the Hydrogen - cave, while vibration , into the Energy – Space - Unit-meters, g, π, creates the Electron, e, and Charges, . General Relativity touches the Planck - length while Quantum Mechanics begun to Penetrate in it. EPR Argument is a Void after the elucidating of the Geometry that is followed.as the Energy analysis the critic on the Fundamental Forces, the what is Energy-Quantization and what is Space-Energy.